Addresses as a bone of contention in ensuring free and fair local government elections - Msaule, P. R. (SAAPAM (South African Association of Public Administration and Management), 2016)
The test for democracy is the regular free and fair elections. In South Africa, in order for one to be eligible to exercise ones right to vote one has to register for elections in the common voters' roll. The settings in which the national and provincial elections on the one hand, and the local government on the other, take place and are conducted are different. Although the IEC has a duty to record the addresses of the voters in the common voters' roll, the importance of the recordal of addresses in the local government elections is the more prominent. This is so because local government elections are conducted on ward basis as opposed to the national and provincial elections that are conducted on party list system. The importance of addresses in the local government elections cannot be underestimated: they assist in ensuring that only voters eligible to vote in particular wards do so. Addresses also enable candidates to canvass the votes from the eligible voters. Although the IEC has a duty to record addresses of the voters such duty arises were the addresses are available. Failure by the IEC would not per se render the elections not to be free and fair. The impact of such irregularity must be proven before the elections could be held not to have been free and fair.
Article
Keywords: Democracy; Elections; IEC; Voters; Democracy; Voting; Local government; Elections -- South Africa